RANCANG BANGUN SEPEDA LISTRIK TERINTEGRASI SISTEM KONTROL KECEPATAN, INTENSITAS CAHAYA, DAN PERINGATAN BAHAYA - Eldoni Tuah Rito Purba; Erni Yudaningtyas; Raden Arief Setyawan (Jurnal Mahasiswa TEUB, 2023)
Electric bicycles in the modern era require useful features to transform transportation into a space for innovation, aiming for energy-efficient, environmentally friendly, and safe riding experiences. This research integrates several features, including the control system for bicycle lighting, hazard warning using a buzzer, PID control for the bicycle motor, and the use of supercapacitors in the battery system. The objective of the research on the bicycle lighting control system is to achieve stable and accurate control of light intensity with an average error rate of 5.887%, a recovery time of 1.032 seconds, and power consumptionranging from 2.784W to 8.664W. The objective of the hazard warning system using a buzzer is to create an automatic warning system based on Mamdani fuzzy logic, where the experimental PWM output matches the PWM output from the fuzzy design in MATLAB. The purpose of the PID control research is to enhance the performance of the bicycle's BLDC motor, aiming to reduce overshoot by 80%, rise time by 50%, and settling time by 50%. The experimental results of the implemented supercapacitor battery system demonstrate a decrease in the maximum voltage output from 42.2V to 35.5V and a reduction in the battery'speak current from 19.1A to 16.9A. Furthermore, the output power exhibits an average decrease from 679.172W to 586.508W. Keywords: PID, Light, Buzzer, Supercapacitor